Learning to mentalize: A mediational approach for caregivers and therapists. Issue 3 (15th April 2020) - Sharp, Carla; Shohet, Cilly; Givon, Deborah; Penner, Francesca; Marais, Lochner; Fonagy, Peter
Abstract: Mentalization‐based therapies (MBTs) are rigorous, theoretically grounded, and evidence‐based interventions. However, dissemination of this psychodynamic informed intervention lags behind that of more skills‐based therapies due to a lack of concrete operationalization of its key components. In this proof‐of‐concept article, we describe how the learning (mediational) components of an educational intervention, the mediational intervention for sensitizing caregivers, can operationalize key components of MBTs in behaviorally anchored ways. We suggest that the process of the recovery of mentalizing can be operationalized through five learning components: focusing, affecting, expanding, rewarding, and regulating. In operationalizing the process of rebuilding mentalizing using these observable, behaviorally anchored concepts focusing on creating epistemic trust, we hope to increase the accessibility of MBTs to a wider audience.